Steady-state thermal hydraulic modelling and turbine trip transient simulation of the NuScale integral pressurised water reactor using the ASTEC code - Guo, Zhexi; Xiao, Sicong; Chung, Keng Yeow (Frontiers in Energy Research, 2022)
A steady state model of the NuScale reactor has been built using the thermal hydraulic module CESAR of the severe accident code ASTEC. Construction of the model was achieved through iterations based on convergence towards data provided by NuScale pertaining to important operating properties—core temperatures, coolant mass flow rate and secondary steam temperature—at 100% power (160 MW) and also at lower power levels. Good agreement with reference values was achieved to within 3% deviation. With a similar methodology, the previous model was adjusted to give a second steady state model meant to provide conservative initial conditions from which a turbine trip transient simulation would be performed. Sound agreement with literature was achieved, with maximum deviations of less than 1.8% for monitored parameters. Lastly, a turbine trip transient was simulated and compared to reference data from analyses performed with NRELAP5 and RELAP5/SCDAPSIM. The most important system behaviors and event timings are well captured and reproduced, with discrepancies arising from inevitable estimates made due to lack of information.